ARBOREOUS SPECIES POPULATION IN A TOPOGRAPHIC GRADIENT OF MIXED OMBROPHILOUS FOREST IN RIO GRANDE DO SUL - Narvaes, Igor da Silva; Longhi, Solon Jonas; Kilca, Ricardo de Vargas; Rodrigues, Tales Eduardo Sangoi (Floresta, 2014)
Abstract This study was part of the Long Term Ecological Project (PELD) conducted in the São Francisco de Paula National Forest, RS where Mixed Ombrophilous Forest is predominant. The aim was to identify distribution of arboreous species depending on different soil conditions occurring in the low, medium and upper slopes of the studied area. 180 sample units of 100 m2 distributed along the topographical gradient were installed, with identification of the totality of arboreous species with 3 cm ≤ CBH < 30 cm and height exceeding 1.30 meters. In addition, thirteen environmental variables were collected in each sub-unit. The Canonical Correspondence Analysis model (CCA) indicated that only the slope, the topographic position, the stoniness and the soil color (up to 50 cm in depth) were the variables that best distinguished the sample groups of the slope environments. Out of the 53 species included in the model, ten species showed best correlations with the typical environments of upper slopes and 12 species were most characteristics of the lower positions, while the remaining resulted well adapted to different hillside topographic conditions. Environmental preferences of the species could be considered in silvicultural and recuperation programs applied to hillside environments of the region. Keywords: Araucarian Forest; species distribution pattern, edaphic characteristics; canonical correspondence analysis. Resumo Ocupação de espécies arbóreas em um gradiente topográfico na Floresta Ombrófila Mista no Rio Grande do Sul. O presente estudo foi parte do Projeto Ecológico de Longa Duração (PELD), realizado na Floresta Nacional de São Francisco de Paula, RS, onde predomina a Floresta Ombrófila Mista. O objetivo foi identificar relações de distribuição das espécies arbóreas em diferentes condições edáficas que ocorrem em posições inferiores, médias e superiores em encostas na área de estudo. Foram instaladas 180 subunidades amostrais de 100 m2 distribuídas ao longo dessas encostas, identificados todos os indivíduos arbóreos com 3 cm ≤ CAP < 30 cm e altura superior a 1,30 metros, além de13 variáveis ambientais inventariadas em cada subunidade. O modelo de Análise de Correspondência Canônica (ACC) indicou que a variação na declividade, na posição topográfica, na pedregosidade e na cor dos solos (na profundidade de até 50 cm) foram as variáveis que melhor distinguiram os grupos de parcelas que caracterizaram os ambientes das encostas. Das 53 espécies inseridas no modelo, dez espécies demonstraram maiores correlações com os ambientes típicos das encostas superiores e 12 espécies foram mais características das posições inferiores, enquanto que as demais apresentaram ampla adaptação às diferentes posições das encostas. As preferências ambientais das espécies poderiam ser consideradas em programas silviculturais e de recuperação nos ambientes de encostas na região. Palavras-chave: Floresta com Araucária; padrão de distribuição de espécies; características edáficas; análise de correspondência canônica.